PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE EKSPERIMEN PADA MATERI PERUBAHAN WUJUD BENDA DI SDN 2 SUMOKEMBANGSRI BALONGBENDO - Shofi’, Zahrotus; El-Yunusi, Muhammad Yusron (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
This study was designed to improve the academic achievement of fourth-grade students at SDN 2 Sumokembangsri regarding the topic of material transformation using experimental techniques. The experimental method was chosen because it allows students to learn actively, conduct direct experiments, observe changes in the form of objects, record results, and draw conclusions independently. This study applied the Classroom Action Research (CAR) method through two cycles, which included stages of planning, implementation, observation, and in-depth evaluation. The research participants involved all students at the fourth-grade level, totaling 30 individuals. The measurement tools applied were learning achievement tests and student behavior recording forms. The study findings revealed significant progress in students' academic achievement, learning enthusiasm, and scientific thinking abilities. There was an increase in the percentage to 100% in the first stage and 97% in the second stage. Observations showed improvements in observation skills, measurement, data analysis, and the ability to explain phenomena sequentially. The experimental method also fostered interest, creativity, and independence. This research proves that experiment-based science learning. This approach proved very successful in encouraging mastery of core ideas, building scientific thinking skills, and stimulating learning enthusiasm among students. Thus, the experimental method becomes an appropriate alternative to optimize science learning in elementary schools. ABSTRAK Studi ini dirancang untuk memperbaiki pencapaian akademik murid kelas empat di SDN 2 Sumokembangsri terkait topik transformasi bentuk materi dengan menggunakan teknik eksperimen. Metode eksperimen dipilih karena memungkinkan siswa belajar secara aktif, melakukan percobaan langsung, mengamati perubahan wujud benda, mencatat hasil, dan menarik kesimpulan secara mandiri. Studi ini menerapkan metode Penelitian Tindakan Kelas (PTK) melalui dua putaran, yang mencakup tahapan penyusunan rencana, implementasi, pengamatan, serta evaluasi mendalam. Peserta penelitian melibatkan semua murid di tingkat kelas IV, dengan total 30 individu. Alat pengukuran yang diterapkan adalah ujian prestasi belajar serta formulir pencatatan perilaku siswa. Temuan studi mengungkapkan kemajuan yang nyata dalam capaian akademik, semangat belajar, serta kemampuan berpikir ilmiah para siswa. Terjadi peningkatan persentase menjadi 100% pada tahap pertama dan 97% pada tahap kedua. Observasi menunjukkan peningkatan keterampilan observasi, pengukuran, analisis data, dan kemampuan menjelaskan fenomena secara runtut. Metode eksperimen juga menumbuhkan tertarik, kreativitas, serta kemandirian. Penelitian ini membuktikan bahwa pembelajaran IPA berbasis percobaan Pendekatan ini terbukti sangat sukses dalam mendorong penguasaan ide-ide pokok, membangun kemampuan berpikir ilmiah, serta merangsang semangat belajar di antara para peserta didik. Dengan demikian, metode eksperimen menjadi alternatif yang tepat untuk mengoptimalkan pembelajaran ilmu pengetahuan di sekolah dasar.